Inovasi Peningkatan Pemahaman Literasi dan Numerasi melalui Pemberian Label Informasi Gizi Makanan pada Kegiatan Jumat Sehat di SD N 2 Temurejo Bangorejo - Rofika, Lutvia Dwi; Trianita, Desi (Pusat Penelitian dan Pengabdian Masyarakat STIKes Banyuwangi, 2025)
Literacy and Numeracy are core skills that must be mastered by elementary school students. Learning with the same method for a long period often cause students quickly bored, including when learning literacy and numeracy at SD N 2 Temurejo Bangorejo. Therefore, making varied learning innovations is the main focus of the teachers at SD N 2 Temurejo. The learning process of literacy and numeracy is not limited, it is highly recommended to utilize the school environment and culture that is already known to all school components, especially students. Healthy Friday is a routine culture carried out every two weeks at SD N 2 Temurejo, where every school component will receive healthy food. This activity aimed to innovate literacy and numeracy learning make the provision of a Nutrition Information Label on food to in the Healthy Friday activity. This activity is carried out by providing nutrition information labels on fruit ice with the composition and nutritional value in it. After being given the nutrition information label, students are required to read and understand each component of the information listed on the label. As a result, in addition to getting healthy food, students also get new learning about the nutritional information of the food they will consume. Reading the nutritional components and nutritional content as a medium for improving understanding of literacy and numeracy learning has never been learned before by the students of SD N 2 Temurejo, therefore, this can be made an exciting learning innovation and have an impact on the literacy and numeracy abilities of elementary school students.